SWOT ANALYSIS OF FINANCIAL TECHNOLOGY IMPLEMENTATION TO ONLINE PEER TO PEER (P2P) LENDING IN INDONESIA - Yuniatin Trisnawati DKW; I Gusti Putu Diva Awatara (Journal of Applied Economics in Developing Countries, 2018)
The development of Financial Tehcnology in Indonesia makes technology-based companies continue to grow. These companies began to be established and registered in the Financial Services Authority (OJK), which is based on an online peer to peer (P2P) lending platform. Financial Services Authority (OJK) data states that as of September 2018, the number of companies engaged in Peer to Peer (P2P) Lending continues to grow to 67 platforms with lender account providers reaching 161,297 entities, the number of borrower accounts (borrower) reaching 2,300,007 entities with low bad credit rates around 1.2%. The process of implementing peer to peer online activities (P2P) lending is done through a website or smartphone application that is downloaded through Google Play Store making it easier for anyone and anywhere to make transactions both as lenders or borrowers. This study discusses the SWOT analysis of online peer to peer (P2P) lending activities in terms of lending companies and individuals both as lenders and borrowers.Keywords: Financial Technology, Online peer to peer (P2P) Lending, SWOT Analysis, Lender, Borrower